SEMI - SOLID AND SOLID PHARMACEUTICAL FORMS BASED ON PASTURE. MICROBIOLOGICAL STUDY - Olimpia Dumitriu Buzia; Mădălina Nicoleta Matei; Aurel Nechita; Gabi Topor; Daniela Laura Buruiană; Crenguța Mihaela Gîrbăcea; Anamaria Zaharescu; Alin Laurentiu Tatu; Gabriela Gurău; Kamel Earar (Romanian Society of Oral Rehabilitation, 2021)
Our work aimed to develop and analyze various semi-solid pharmaceutical forms, such as mucilages, ointments, but also solids, respectively trochists associated with pasture. This is also the novelty of our study, that is, the incorporation of pasture in various pharmaceutical forms, followed by microbiological analysis and analysis of the stability over time of these pharmaceutical forms. Subsequently, we analyzed these pharmaceutical forms physically and chemically, as well as microbiologically on various microbial strains such as gram-positive germs: Staphylococcus aureus (reference strain 25293), Streptococcus pneumoniae (reference strain 49616), Streptococcus Pyogenes (reference strain ); Enterococcus casselifavus (Reference strain 700327); gram negative germs: Escherichia coli (Reference strain 25922); Pseudomonas aeruginosa (Reference strain 27853); Enterobacter hormaechei (Reference strain 700323); Klebsiella pneumoniae (700 strain) ; fungi: Candida albicans (Reference strain 90028). We used different amounts of pasture, respectively 2g and 5g embedded in trochists. Trochists prepared with sugar and water had a good antimicrobial activity compared to E.Coli ATCC25922. On the strain of Staphyloccocus aureus ATCC25923, the highest activity was presented by the trocysts with gelatinous mass and sugar. The best inhibitory activity had the ointment with macrogol, the trocysts with gelatinous mass and sugar and the trocysts with gelatinous mass and sacharum lactis ( inhibition zones 20mm, 21mm, respectively 20mm). In the case of pharmaceutical forms prepared with 5g of raw pasture on Gram-negative bacteria, the best antimicrobial activity was presented by trocysts with gelatinous mass and sugar on Enterobacter hormachei ATCC700323, and on Staphyloccocus aure ATCC25923 as Gram positive germs. Good results were also obtained on Candida albicans ATCC90028, in the case of trochis with sugar